Robust stabilization of competing species in the chemostat. (March 2020) - Reis de Souza, Alex; Efimov, Denis; Polyakov, Andrey; Gouzé, Jean-Luc
Highlights: Coexistence of multi-species in a continuous bioreactor can be assured by using feedback control. While coexisting, these species can be stabilized in a finite-time using sliding-mode control. By means of the proposed methodology, robustness against bounded parametric uncertanties on the kinetic rates are easily compensated. Time-varying fluctuations on the kinetic rates' parameters are shown to be easily tackled. Abstract: This work addresses the problem of robust stabilization of the concentrations of two different species of living organisms, which compete for a single limiting substrate in a bioreactor. This stabilization is performed using discontinuous feedback control laws that ensure the coexistence of all species. The control laws are designed considering bounded parametric uncertainties on the kinetic rates.